Production and optimization of carboxymethyl cellulase and filter paperase of locally isolated Streptomyces lucitanus C5/2 under submerged fermentation of napier grass - Manap, Shahirah (2017)
Lignocellulosic biomass materials are known as a sustainable, renewable feedstock for biofuels production due to domestically abundant and low-production-cost derived from non-food sources. However, due to complex molecular structures of the cellulose, it becomes difficult to hydrolyze into fermentable sugar as the feedstock. The bioconversion of cellulose to fermentable sugar can be catalyzed by a group of enzymes known as cellulolytic enzymes, which is commonly produced by microorganisms (fungi, bacteria, and protozoa). Cellulolytic enzymes system mainly comprised of endoglucanase (carboxymethyl cellulase), exoglucanase, and β- glucosidase enzymes which react together to perform complete hydrolysis process. Grass species are one of cheap lignocellulosic biomass that can be used as energy source in many bioprocesses and industrial applications. Napier grass, scientific name Pennisetum purpureum sp is one of the potential carbon sources, which can be utilized as a substrate for the production of bio-product. The potential of Napier grass as a fermentation substrate was investigated throughout this study. Isolation and identification of the cellulolytic producing bacteria were carried out by initially searching the bacteria from various environmental sources (cattle waste compost, decayed wood and ponds). The cellulolytic enzymes biosynthesis by the selected bacteria isolate using Napier grass as a substrate in submerged fermentation was carried out in batch cultivation using 250 mL shake-flask. The investigations were followed by statistical optimization using response surface methodology (RSM) approach to obtain the optimized cultural conditions and medium composition for maximum activities of carboxymethyl cellulase (CMCase) and filter paperase (FPase). For the assessment of crude enzyme produced, enzymatic hydrolysis of Napier grass was performed by using untreated and treated (1.4M H2SO4 and 7% NaOH) Napier grass to investigate the total reducing sugar production. A total of twenty- five (25) bacterial isolates were grown on the selective media and only six (6) bacterial isolates showed positive results by exhibiting clear zone on carboxymethyl cellulose (CMC) agar plates, which indicate the enzymes production. The C5/2 isolate was selected as the best cellulolytic enzymes producer due to the highest enzyme activities obtained during the quantitative screening and molecularly identified as Streptomyces lucitanus by 16S rDNA sequencing. The optimum values of the fermentation parameters for CMCase and FPase biosynthesis based on the statistical optimization was determined at initial pH of 7.8, agitation speed 170 rpm, inoculum size 19.7% (v/v) and Napier grass concentration 4.30% (w/v) with maximum activities 7.362 U/mL and 2.895 U/mL, respectively which were close to the predicted values. The production of CMCase and FPase shows improvement, 66% and 30%, respectively by application of the optimum values of parameters during the cultivation. The total reducing sugar produced from enzymatic hydrolysis by using treated Napier grass (1.4M H2SO4; 6.541 mg/mL, 7% NaOH; 27.449 mg/mL) as a substrate is higher compared to the untreated Napier grass (1.776 mg/mL). It can be concluded that the newly isolated S. lucitanus C5/2 was able to produce appropriate amount of CMCase and FPase using raw Napier grass as the substrate and significantly improved enzyme activities after statistical optimization by RSM was employed. In addition, the crude cellulolytic enzyme produced by S. lucitanus C5/2 has proven to possess potential application in the hydrolysis of lignocellulosic biomass as Napier grass was been used for production of fermentable sugar. From this investigation, Napier grass shows a good fermentation substrate that it can be fully utilized for the production of bio-product.